Communication Strategy of the Indonesian Kabaddi Federation (FOKSI) Central Java for Image and Popularity - Bungaran Saragih; Limpad Nurrachmad (Universitas Negeri Semarang, 2026)
Research on sport communication has concentrated on established mainstream sports, leaving emerging sport organizations underexplored. This study analyzes how the All-Indonesia Kabaddi Sports Federation (FOKSI) of Central Java builds kabaddi image and popularity, an emerging sport facing low recognition and limited media exposure. A constructivist interpretive qualitative case study was conducted; data were gathered through semi-structured interviews and docu-mentation from eight informants and analyzed thematically following Miles and Huberman. The findings reveal an